Exploring the Correlation Between Students’ Interest in Listening and Listening Comprehension in English Context - Widia Yunita; Jumiyanti Jumiyanti (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
The beginning of human learning is from hearing, thus, many educational experts and educational theories claim that the first learning activity is auditory. The influence of students’ listening comprehension, such as cognitive factors and psychological aspects also involved. One of the psychological problems is students’ interest. The purpose of this research is to find out a significant correlation between students’ interest in listening and their listening comprehension on the eleventh-grade students of SMKN 3 Tanah Putih, Rokan Hilir. The sample of this research was 26 students. The technique used in this research was correlational. In collecting the data, this research was distributing questionnaires to the respondents to assess students’ interests. Aside from assessing students’ listening comprehension, this research conducted a listening test for the students. In analysing the data, the questionnaires were assessed by Likert’s scale rating. The result of this research showed that the score of Sig. (2-tailed) gathered from SPSS 22, it was found that Sig. (2-tailed) the result was 0.001. Because of Sig. (2-tailed) was smaller than 0.05, it can be concluded that the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted, which states there is a significant correlation between students’ interest in listening and their listening comprehension. In conclusion, there is a positive correlation between students’ interest in listening and their listening comprehension. It means that students with higher interest will get better listening comprehension than the lower one. In other words, the higher the interest of students, the better listening comprehension can be achieved.